2002
DOI: 10.1128/mcb.22.21.7398-7404.2002
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Death and Motor Disorders in Mice Congenitally Deficient in Calnexin Expression

Abstract: Calnexin is a ubiquitously expressed type I membrane protein which is exclusively localized in the endoplasmic reticulum (ER). In mammalian cells, calnexin functions as a chaperone molecule and plays a key role in glycoprotein folding and quality control within the ER by interacting with folding intermediates via their monoglucosylated glycans. In order to gain more insight into the physiological roles of calnexin, we have generated calnexin gene-deficient mice. Despite its profound involvement in protein fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 23 publications
3
112
0
Order By: Relevance
“…These mice exhibit motor disorders owing to a loss of large myelinated nerve fibers. 32 The UPR is a ubiquitous mechanism for adapting to ER stress, and BiP is an essential component of this system. However, at various developmental stages, some cell types require specific UPR signaling systems 33 and chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…These mice exhibit motor disorders owing to a loss of large myelinated nerve fibers. 32 The UPR is a ubiquitous mechanism for adapting to ER stress, and BiP is an essential component of this system. However, at various developmental stages, some cell types require specific UPR signaling systems 33 and chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, several reports demonstrated that calnexin is involved in apoptosis induced by ER stress (Delom et al, 2006;Delom et al, 2007;Guerin et al, 2008;Takizawa et al, 2004;Tomassini et al, 2004;Torgler et al, 1997;Zuppini et al, 2002). Intriguingly, the knockout of the gene encoding calnexin in different organisms results in diverse phenotypes (Denzel et al, 2002;Lee et al, 2005;Muller-Taubenberger et al, 2001). These phenotypes, however, have not unveiled comprehensive aspects of the novel cellular roles of calnexin because the organisms studied also encode calreticulin, a paralog that is a luminal ER protein and whose functions overlap with calnexin (Anelli and Sitia, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Calnexin knockout mice die during the early postnatal period, between birth and three months of age. These mice exhibit motor disorders due to a loss of large myelinated nerve fibers (Denzel et al, 2002). Mutant BiP predominantly affected dedicated secretory cells, such as alveolar type II cells and Cajal-Retzius cells, in which active secretion is particularly important.…”
Section: Resultsmentioning
confidence: 99%